Sexual Activity and Impairment in Women with Systemic Sclerosis Compared to Women from a General Population Sample - Levis, Brooke; Burri, Andrea; Hudson, Marie; Baron, Murray; Thombs, Brett D.; Canadian Scleroderma Research Group (CSRG) (PLOS ONE, 2012)
Objective Reports of low sexual activity rates and high impairment rates among women with chronic diseases have not included comparisons to general population data. The objective of this study was to compare sexual activity and impairment rates of women with systemic sclerosis (SSc) to general population data and to identify domains of sexual function driving impairment in SSc. Methods Canadian women with SSc were compared to women from a UK population sample. Sexual activity and, among sexually active women, sexual impairment were evaluated with a 9-item version of the Female Sexual Function Index (FSFI). Results Among women with SSc (mean age = 57.0 years), 296 of 730 (41%) were sexually active, 181 (61%) of whom were sexually impaired, resulting in 115 of 730 (16%) who were sexually active without impairment. In the UK population sample (mean age = 55.4 years), 956 of 1,498 women (64%) were sexually active, 420 (44%) of whom were impaired, with 536 of 1,498 (36%) sexually active without impairment. Adjusting for age and marital status, women with SSc were significantly less likely to be sexually active (OR = 0.34, 95%CI = 0.28–0.42) and, among sexually active women, significantly more likely to be sexually impaired (OR = 1.88, 95%CI = 1.42–2.49) than general population women. Controlling for total FSFI scores, women with SSc had significantly worse lubrication and pain scores than general population women. Conclusions Sexual functioning is a problem for many women with scleroderma and is associated with pain and poor lubrication. Evidence-based interventions to support sexual activity and function in women with SSc are needed.